PENGUATAN KEWENANGAN DPD RI DALAM BIDANG FUNGSI PENGAWASAN - Muchtar Pakpahan (Fakultas Hukum Universitas Kristen Indonesia, 2015)
DPD as the state institution that be created from the spirit of reform in order to make the development of of local area fast or rapid as same as the house of representative and president so, DPD also must have an authority in discussing the draffy of laws mainly that related to the autonomy of local area , relation between the national and local area, the establishment , the enlargement, and the merger local area, the management of nature resource and other economic resource.Kata kunci: Penguatan kewenangan DPD RI